The Gravity Probe B test of general relativity. (17th November 2015) - Everitt, C W F; Muhlfelder, B; DeBra, D B; Parkinson, B W; Turneaure, J P; Silbergleit, A S; Acworth, E B; Adams, M; Adler, R; Bencze, W J; Berberian, J E; Bernier, R J; et al.
Abstract: The Gravity Probe B mission provided two new quantitative tests of Einstein's theory of gravity, general relativity (GR), by cryogenic gyroscopes in Earth's orbit. Data from four gyroscopes gave a geodetic drift-rate of −6601.8 ± 18.3 marc-s yr −1 and a frame-dragging of −37.2 ± 7.2 marc-s yr −1, to be compared with GR predictions of −6606.1 and −39.2 marc-s yr −1 (1 marc-s = 4.848 × 10 −9 radians). The present paper introduces the science, engineering, data analysis, and heritage of Gravity Probe B, detailed in the accompanying 20 CQG papers.